Tindak Tutur Ilokusi dalam Buku Humor Membongkar Gurita Cikeas Karya Jaim Wong Gendeng dan Implikasinya dalam Pembelajaran Bahasa Indonesia - HQ, Sherry; Agustina, Agustina; Juita, Novia (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was to describe the shape, function and strategies used in the book tells of humor Cikeas Octopus Dismantling works Wong Gendeng Jaim. The data of this study is ilokusi speech acts. Sources of data in this study is the book of humor Cikeas Octopus Dismantling works Wong Gendeng Jaim. Data were collected by using a technique that helped with my recording format. The findings of the study are (1) a form of speech act ilokusi found as many as 71 utterances, which consist of expressive speech acts and commissive directive representative, (2) the function of speech acts speech ilokusi found as many as 68, which consists of competitive functionality, pleasure cooperating and conflicting functions and (3) by 67 utterances strategy, which consists of BTTB, BTDBKP, BTDBKN and BSS.